Nurse Employment in Some Countries in the World and in Turkey - Kübra Soydaş; Arzu Kader Harmancı Seren (Association of Nurse Managers, 2023)
For a well-functioning health system, employing a sufficient number of appropriately qualified nurses is essential. The quantity and quality of nursing care are affected by the physical conditions of the workplace, support services, information systems, administrative practices, training and experience of nurses, care delivery models, and the number of nurses in the unit. Many criteria have been developed considering these different variables. These criteria are used in line with the health policies of each country. The aim of this review is to offer a framework for the employment policies of nurses in the world and Turkey.